Hemiataxia: A Novel Presentation of Anti-NMDA Receptor Antibody Mediated Encephalitis in an Adolescent. (3rd December 2017) - Phillips, Greg D.; Jones, Gillian N.; Callaghan, Maureen; DiFazio, Marc P.
Abstract : Anti-NMDA receptor antibody associated encephalitis as a cause of new-onset neuropsychiatric manifestations in children and adults can represent a significant diagnostic challenge for clinicians. Clinical signs often include encephalopathy, new-onset psychosis, and movement phenomenon. Although orofacial dyskinesias were initially identified as a characteristic movement phenomenon in this type of encephalitis, an expanded range of abnormalities has recently been reported, including isolated ataxia. We report a case of isolated hemiataxia in a young adult with mild initial psychiatric manifestations. A personal and family history of preceding neuropsychiatric symptoms produced diagnostic confusion and resulted in a significant diagnostic and therapeutic delay. Our case confirms the unilateral movement manifestations that have been emphasized in recent reports. Additionally, it confirms the need for involvement of neurologic as well as psychiatric services in the evaluation of such cases and emphasizes the importance of the neurologic examination in presentations with an initial psychiatric predominance.